Market for attention consequences of informational gaps on performance of mass media - Palguta, Ján; Tegze, Miron, 1954-; Kollár, Miroslav; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2008)
In my dissertation I examine the mutual relationship between a company in mass media market and its customers, where the company enjoys an informational advantage over its customers about the quality of the provided information goods. The mass media companies compete for customers? attention, i.e. for the total number of watchers, readers, subscribers, etc., because that determines their profits. The document analyses the market mechanisms under information asymmetry and adds to the standard analysis of supply and demand the notion on the quality of the exchanged service. The principal aim of this work is to economically explain the contemporary trends of scandal-mongering, sensationalism, unprofessional and unethical practices in the mass media market and by the reputation theory describe the behaviour of companies trying to protect their goodwill. The work comments on the welfare implications of the existing market structure and it suggests procedures available for overcoming of the information asymmetry.
Vedoucí práce: Miron Tegze
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2008
Rok obhajoby 2008
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses